VD_FINDINFO Jug-inc / 2010 / 56 vom 2. Juli 2010 - VD Tribunal cantonal (2010)
DROIT D'ÊTRE ENTENDU, COMPÉTENCE, PROROGATION DE FOR, LITISPENDANCE, CONNEXITÉ MATÉRIELLE | 17 ch. 1 CL, 18 CL, 21 CL, 22 CL, 5 ch. 3 CL, 6 ch. 1 CL, 119 CPC, 149 al. 4 CPC, 177 al. 1 CPC, 29 al. 2 Cst., 9 al. 2 LDIP